The association between meniscal body extrusion and the development/enlargement of bone marrow lesions on knee MRI in overweight and obese women. Issue 3 (January 2020) - Zhang, Fan; Bierma-Zeinstra, Sita M.; Oei, Edwin H.G.; Turkiewicz, Aleksandra; Englund, Martin; Runhaar, Jos
Abstract: Objective: To determine the association between meniscal body extrusion and bone marrow lesion (BML) development/enlargement in overweight and obese women at high risk of knee osteoarthritis (OA). Design: We used baseline and 30 months follow-up data of the PROOF study, Netherlands, comprising overweight or obese women aged 50–60 years, free of clinical knee OA. All subjects (n = 395) completed a questionnaire on knee complaints and physical activity, underwent physical examination, radiography, and repeated 1.5 T MRI of both knees. Using the mid-coronal MRI slice, one observer measured tibial plateau width and meniscal body extrusion of both menisci in both knees. BMLs and meniscal damage were read using the semi-quantitative MOAKS scoring system by another observer. The association between BML development and meniscal extrusion was primarily analyzed with a random-effects logistic regression model adjusted for age, body weight, body height, physical activity, meniscus damage, knee alignment, and tibia width. In addition, we used a fixed-effect regression model for evaluation of knee-specific factors. Results: In our primary model, there was about 24% increased risk of BML incidence/enlargement per 1 mm extrusion (95% confidence interval [CI] 0.99, 1.57) for medial compartments and 69% risk increase (95% confidence interval [CI] 1.27, 2.25) for the lateral compartments. Results from the fixed-effects regression model were similar, strengthening the validity of the findings. Conclusions: Meniscal body extrusion is an important factor influencing BML development/enlargement, and thus may be a potential treatment target in knee OA development.